Extra-renal Transplanted Kidney Stone: Case Presentation and Literature Review - Basiri, Abbas; Nadjafi Semnani, Mohammad; Mohseni Rad, Hamed (Urology Journal, 2018)
Soft tissue calcification is common in uremic patients. Wound calcification or ossification is not so prevalent except in specific conditions like inflammation and ischemia or wound tension. We present a 40-year-old transplanted patient, not only perirenal ossification but also with multiple perirenal stones. The presentation was severe pain on the site of transplantation. Pre-op CT scan revealed perirenal calcified mass. Intraoperative finding was very thick tissue accompanied with a lot of stones around the transplanted kidney. The patient had history of ureteral fistula after renal transplantation that needed temporary percutaneous nephrostomy and then uretero-neocystomy. It seems that urinary leakage through nephrostomy site probably is the predisposing factor for stone formation around the kidney where as there is no stone inside the Kidney.